1994
DOI: 10.1093/jn/124.3.444
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Reduces the Efficacy of Tryptophan as a Niacin Precursor

Abstract: A niacin-deficient purified amino acid diet that contained adequate (40 mg/kg) or deficient (10 or 15 mg/kg) iron was used to assess the growth promoting efficacy of tryptophan as a niacin precursor. Basal diets contained 1400 mg/kg tryptophan, a level that was established as meeting the requirement for tryptophan per se in diets containing excess nicotinic acid. Chicks fed the iron-deficient diets had markedly lower hemoglobin concentrations than those fed the iron-adequate diets. Regardless of iron level, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In accordance with our results, hypoalbuminaemic patients ordinarily stay longer time in hospital and show increased mortality (Cunha et al, 1999). Higher anaemia frequency among malnourished pellagra could, at least partially, be caused by inadequate intake of bioavailable iron, in accordance with high iron de®ciency among malnourished alcoholics, and reduced tryptophan utilisation as a niacin precursor in iron de®ciency (Oduho et al, 1994).…”
Section: Discussionsupporting
confidence: 89%
“…In accordance with our results, hypoalbuminaemic patients ordinarily stay longer time in hospital and show increased mortality (Cunha et al, 1999). Higher anaemia frequency among malnourished pellagra could, at least partially, be caused by inadequate intake of bioavailable iron, in accordance with high iron de®ciency among malnourished alcoholics, and reduced tryptophan utilisation as a niacin precursor in iron de®ciency (Oduho et al, 1994).…”
Section: Discussionsupporting
confidence: 89%
“…Also, vitamin D is required for efficient absorption of both Ca and P. The interactions between Zn and Cu; Mo and Cu; Zn and Fe; cysteine or ascorbate and Cu, Zn, or Fe; Mn and P; Se and vitamin E; I and Br; As and cysteine; phytates or oxylates and several macro-and micromineral elements have been identified and help explain the utilization efficiencies of mineral elements in various foods (3). Among the vitamins, animals were used to help us understand the tryptophan 3 niacin and lysine 3 niacin interactions (4,5) as well as the effect of Fe deficiency on the conversion efficiency of tryptophan to niacin (6). Also, progress in solving pellagra in humans was held back for many years because of lack of a suitable animal model.…”
Section: Nutrient-nutrient Interactionsmentioning
confidence: 99%
“…A study in rhesus monkey found that the NAD metabolites were similar between IDA and control groups, and NAD pathway components nearly doubled after the treatment of IDA 34 . Another study in male chicks found that iron deficiency reduced the utilization of tryptophan with which de novo biosynthesis of NAD starts 35,36 . Haemolytic anaemia could be induced by medications along with other causes, whose late diagnosis could be fatal 37 .…”
Section: Discussionmentioning
confidence: 99%
“…34 Another study in male chicks found that iron deficiency reduced the utilization of tryptophan with which de novo biosynthesis of NAD starts. 35,36 Haemolytic anaemia could be induced by medications along with other causes, whose late diagnosis could be fatal. 37 Nicotinamide mononucleotide adenylyltransferase 3 (Nmnat3) is considered a NAD synthesis enzyme involved in de novo and salvage pathways.…”
Section: Discussionmentioning
confidence: 99%